STRUCTURAL TRANSFORMATION OF THE POLISH STATE AGRICULTURE SECTOR IN THE LOWER SILESIA REGION AFTER 1991 - Wawrzyniak, Sylwester; Ogły, Krystian (Acta Scientiarum Polonorum. Oeconomia, 2002)
Structural changes in the agriculture of Poland were triggered by a difficult situation of the state-owned farms in the late eighties. The crucial factor of changes in the agrarian structure of Lower Silesia in the period of 1992-2000 was a land lease. There were also other important factors like a sale of the land or other forms of land’s allocation. Due to the restructuring there was a significant growth of the acreage in the individual farmers’ sector. Within 2000, 91.26% of land owned by a local APA section in Wrocław were allocated and 8.74% still needs to be allocated.